Responses of oil degrader enzyme activities, metabolism and degradation kinetics to bean root exudates during rhizoremediation of crude oil contaminated soil - Yang K.M. (2023)
During rhizoremediation process, plant roots secrete the specific exudates which enhance or stimulate growth and activity of microbial community in the rhizosphere resulting in effective degradation of pollutants. The present study characterized cowpea (CP) and mung bean (MB) root exudates and examined their influences on the degradation of total petroleum hydrocarbons (TPHs) and polycyclic aromatic hydrocarbons (PAHs) by the two oil degraders Micrococcus luteus WN01 and Bacillus cereus W2301. The effects of root exudates on soil microbial population dynamic and their enzymes dehydrogenase (DHA), and catechol 2,3 dioxygenase (C23O) activities were assessed. Both root exudates enhanced the degradation by both oil degraders. Cowpea root exudates maximized the removal of TPHs and PAHs by M. luteus WN01. Both bacterial population and DHA increased significantly in the presence of both root exudates. However, the C23O activities were significantly higher in WN01 treated. No significant influence of root exudates was observed on the C23O activities of W2301 treated. By using gas chromatography -mass spectroscopy, the dominant compounds found in cowpea and mung bean root exudates were 4-methoxy-cinnamic acid and terephthalic acid. Found in lower amount were propionic, malonic acid, and citric acid which were associated with enhanced PAHs desorption from soil and subsequent degradation. Novelty statement This is the first study to characterize the low molecular weight organic acids from root exudates of cowpea and mung bean and their influences on hydrocarbon desorption and hence enhancing the biodegradation process. The findings of the present study will greatly contribute to a better understanding of plant-microbe interaction in total petroleum hydrocarbons contaminated soil.